A Conceptual Exploration on the Samprapti Ghatakas of Hyperthyroidism (International Journal of Ayurveda and Pharma Research, 2022)
Thyroid disorders are the commonest endocrine disorders worldwide with devastating health consequences. Hyperthyroidism is commonly referred as an overactive thyroid which enhances the rate of metabolism in multiple levels. Since this disorder is having multisystem effects, the pathology can’t be restricted to the gland only. There is striking similarity between the functions of Dhatwagni and thyroid hormone metabolism. The far reaching metabolic disturbances in thyroid dysfunctions are attributed to Dhatwagni vikruthi. On a close review, it is evident that Ayurvedic concept available in this direction clearly demonstrates the pathology when juxtaposed against the advanced principles of modern medicine. In Ayurveda, the categorization of diseases had been made according to the involved Doshas, Dooshyas, Srotas, Agni, Ojus (the etiopathological factors) which are termed as the Samprapti ghatakas. These descriptions are largely based on factors and way of life prevalent in the period when they were compiled. Detailed studies may be undertaken to ascertain these factors of the diseases which are relevant in the current lifestyle and environment. It is striking that the treatment of hyperthyroidism has not changed greatly in the past several decades. Only conservative management is possible through Anti thyroid drugs, but about a 50% have relapse rate. A global epidemiological study reported a data of 50% of subclinical hyperthyroid subjects have arisen from excessive intake of thyroid hormones. A thorough understanding of the complete disease process with regard to the Samprapti ghatakas involved is of great importance in this subject which forms the basis of systematic approach in the Ayurvedic management.